2013
DOI: 10.1589/jpts.25.915
|View full text |Cite
|
Sign up to set email alerts
|

Activities of the Vastus Lateralis and Vastus Medialis Oblique Muscles during Squats on Different Surfaces

Abstract: [Purpose] The purpose of the present study was to examine the effects of squat exercises performed on different surfaces on the activity of the quadriceps femoris muscle in order to provide information on support surfaces for effective squat exercises. [Subjects and Method] Fourteen healthy subjects performed squat exercises for five seconds each on three different support surfaces: hard plates, foam, and rubber air discs. Their performance was measured using electromyography. As the subjects performed the squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…In the present study, the WBT were selected based on their wide application related to practicality, functionality, and efficiency in promoting strengthening of lower limb muscles. Dynamic squatting exercises have been studied as important tools for rehabilitation programs, primarily those utilizing knee EMG 9 ) . According to our results, the 2 vasti muscles produce approximately 50% more activity than the RF during WBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the WBT were selected based on their wide application related to practicality, functionality, and efficiency in promoting strengthening of lower limb muscles. Dynamic squatting exercises have been studied as important tools for rehabilitation programs, primarily those utilizing knee EMG 9 ) . According to our results, the 2 vasti muscles produce approximately 50% more activity than the RF during WBT.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that deserves mention is the similarity between the EMG activation patterns of the vasti muscles. Considering that healthy adults with normal knees show VM/VL ratios of close to 1 9 ) , the study subjects had adequate EMG behavior for these muscles (healthy subjects). These findings could also justify the insufficiency of real-time feedback to promote additional improvements in EMG activation patterns of the quadriceps.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because the delayed activity of the VMO is less than the lateral force vector produced by the VL, the iliotibial band and knee bones tend to be pulled laterally 4 ) . Hyong and Kang 5 ) observed that performing a squat on an unstable base of support, such as rubber, affects the selective activity of the VMO. Irish et al 6 ) report that a squat accompanied by isometric hip joint adduction using a pillow is effective for the selective activation of the VMO.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, previous studies have aimed to selectively activate the VMO by applying squatting. To selectively activate the VMO, Hyong and Kang 5 ) applied squats on diverse bases of support, such as a hard plate, form, and rubber air disc. Meanwhile, Irish et al.…”
Section: Introductionmentioning
confidence: 99%
“…Patellofemoral pain syndrome is a disease in which the patellar medial pulling force is weakened due to a weak vastus medialis and the patella is dislocated laterally, so it causes knee pain 6 , 10 ) . Patients with this syndrome are treated with selective strength training programs for the vastus medialis in order to decrease pain and treat the disease 11 , 12 , 13 ) , and a lot of research has been performed to identify ways to improve the vastus medialis selectively 14 , 15 , 16 ) . Thus, the muscle imbalance between the vastus medialis and lateralis could cause pain, and training programs to relieve the muscle imbalance are needed if there are imbalances between these two muscles according to knee alignment.…”
Section: Introductionmentioning
confidence: 99%